PENGARUH MOTIVASI, LOYALITAS, PENGALAMAN DAN USIA TERHADAP PRODUKTIVITAS KERJA KARYAWAN AMIK HASS BANDUNG - Budiman, Arif (STMIK Amiko Purwokerto, 2008)
AMIK HASS Bandung as the formal higher education agency of the Diploma Computer Program that will compete in the netting of the new student and printed human resources was ready the work, must realise that the importance of the understanding about the level of the work motivation of the employee, the employees loyalty, the work experience and the age of the employee to measure the productivity of the work.Make aware this matter above, then specially in this research will be inspected four variable free (independent) that is: the motivation (X1), loyalty (X2), the experience (3) and the age (X4) against variable was tied (dependent) that is: the productivity of the work of the employee AMIK HASS Bandung.To four variable free this was suspected of having relations that were strong towards the productivity of the work of the employee AMIK HASS Bandung. From the price of the analysis of the dual determination coefficient (R2) = 0.887 that meaning that 88.7% highness or lowness of the productivity of the work were affected (was caused) by the change in the motivation, loyalty, the age and the work experience together, whereas 11.3% the rest of them as a result of by variable other. Whereas results of the testing were against this dual determination coefficient shown by the price of F = 58.62 with the significant level = 0.0001. So could be concluded that together the motivation, loyalty, the age and the work experience had the influence that was strong and significant towards the productivity of the work :The next one of the prices of the partial regression coefficient were received by the equality of linear regression as follows: ZY = 0.314 ZX1+ 0.275 of ZX2 + 0.822 of ZX3 â 0.391 of ZX4 Sig : 0.003 0,019 0,003 0,115 To variable X4 had the significant level > 0.05 meaning that partially the work experience did not have the influence on the productivity of the work and X3 (the age) was variable that was dominant his influence on the productivity of the work.Therefore could be suggested to increase the productivity of the work of the employee, the agency could make the formulation stimulan-stimulan that was matched with the requirement for the employee and the agency capacity. As for attention of the agency better be focused on the dimension of the age because of this variable that was dominant his influence on the productivity of the work. The step that could be carried out was by giving the addition of the authority and the belief to the employee